Potassium Uranyl Vanadate, KUO2 VO4 - Jiménez de Abeledo, M. E.; Rodríguez de Benyacar, M. A.; Poljak, R. J. (American Chemical Society, 1958)
Fil: Jiménez de Abeledo, M. E. Comisión Nacional de Energía Atómica; Argentina